Prostate cancer diagnosis and management: current practices in Africa a consultant-based survey - Biyouma, Marcella Derboise Christelle; Gebreselassie, Kaleab Habtemichael; Abdelkerim Nedjim, Saleh; Ziba, Ouima Justin Dieudonné; Makon, Axel Stéphane Nwaha; Kifle, Anteneh Tadesse; Mohammed, Taofiq Olayinka; Cassell, Ayun Kotokai; Youssef, Bencherki; Idrissa, Sissoko; Mbwambo, Orgeness Jasper; Mahamat, Mahamat Ali; et al. (Frontiers in Urology, 2025)
IntroductionIn Africa, prostate cancer poses significant diagnostic and treatment challenges due to limited access to diagnostic tools and healthcare resources. This survey aimed to assess current prostate biopsy practices, patient classification methods, and available therapeutic means among African urologists to propose strategies for improved screening, diagnosis, and management.MethodsA web-based self-administered questionnaire was distributed to urologists in 58 African centres, focusing on biopsy practices, cancer diagnosis, management, and treatment protocols. After pretesting and validation, data collection spanned six weeks, followed by duplicate elimination and arithmetical analysis, with results expressed in absolute, mean, or percentage values.ResultsFeedback was received from 58 centres across diverse African regions, including Central, Southern, West, East Africa, and Madagascar, comprising general, private, and university hospitals. Prostate cancer emerged as the most frequent urological cancer in all regions studied. The assay for prostate-specific antigen (PSA) was available in nearly all centres. Biopsy techniques varied, with ultrasound-guided biopsies being the most common (30 centres), followed by digital-guided (20 centres) and MRI-guided biopsies (5 centres). One centre lacked the expertise to perform biopsies. Radiological workup availability was high, with CT available in 56 centres, MRI in 54, PET scans in 14, and scintigraphy in 29. Treatment capabilities varied, with 53.4% of centres able to perform radical prostatectomies, 86.2% offering radiotherapy, and 94.8% providing medical castration. Among the centres, 56 performed fewer than 5 radical prostatectomies per month, while only 2 centres performed between 5 and 10 per month.ConclusionIt is important to standardise prostate cancer diagnosis and treatment protocols across Africa while improving access to advanced diagnostic technologies and treatment facilities. Implementing these changes could enhance early detection, improve treatment outcomes, and reduce the burden of prostate cancer in Africa.